Pengaruh Pelatihan dan Kompentesi terhadap Prestasi Kerja Pegawai pada Dinas Perhubungan Kota Bima - Sendarina; Firmansyah Kusumayadi; Feni Aryani (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study aims to analyze the influence of training and competence on employee performance at the Bima City Transportation Agency. The research background stems from preliminary findings indicating the low effectiveness of training programs and varying levels of employee competence, which impact the quality of public services. This study employs a quantitative approach with an associative research design. The population consists of 189 employees of the Bima City Transportation Agency, with a sample of 34 civil servants selected using a purposive sampling technique. Data were collected through observations, Likert-scale questionnaires, and literature studies, and analyzed using multiple linear regression with the assistance of SPSS 21.0. The results reveal that training does not have a significant effect on employee performance, whereas competence has a significant partial effect. Simultaneously, training and competence significantly affect employee performance with a coefficient of determination of 97.6%, while the remaining 2.4% is influenced by other factors outside the model. These findings highlight the importance of strengthening employee competence and evaluating the design of training programs to ensure their relevance to job requirements and technological developments. The study is expected to provide practical insights for the Bima City Transportation Agency in formulating more effective and adaptive human resource development strategies.